Empirical evaluation of different classroom spaces on students' perceptions of the use and effectiveness of 1‐to‐1 technology. (1st December 2016) - Byers, Terry; Hartnell‐Young, Elizabeth; Imms, Wesley
Abstract: This study explored the effect of different classroom spatial layouts on student perceptions of digital technology in a secondary schooling environment. A quasi‐experimental approach facilitated by a Single Subject research design (SSRD) isolated the impact of two learning spaces—traditional' classrooms, and 'new generation learning spaces' (NGLS), on students' perceived effectiveness, use and value of one‐to‐one technology as a learning tool. Results from quantitative analyses over the period of a school year indicated that different spatial configurations had a measurable effect on how students' perceived the effectiveness of the affordances of digital technology, with improvements often linked to NGLS. However, the evidence suggests that a change in learning space alone will not increase learning. A change in space supports those teachers who are able and willing to integrate the affordances of technology into their practice. Building on the collective methodologies of earlier work this analysis has reinforced the credibility of this unique methodological approach, arguing this evaluative strategy offers the capacity to generate much needed robust empirical data on evaluation of learning environments in a secondary school setting.